2019
DOI: 10.1371/journal.ppat.1007926
|View full text |Cite
|
Sign up to set email alerts
|

Trickle infection and immunity to Trichuris muris

Abstract: The majority of experiments investigating the immune response to gastrointestinal helminth infection use a single bolus infection. However, in situ individuals are repeatedly infected with low doses. Therefore, to model natural infection, mice were repeatedly infected (trickle infection) with low doses of Trichuris muris. Trickle infection resulted in the slow acquisition of immunity reflected by a gradual increase in worm burden followed by partial expulsion. Flow cytometry revealed that the CD4+ T cell respo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 53 publications
7
39
1
Order By: Relevance
“…Therefore, during a trickle infection the concentration of these alarmins may increase with each subsequent challenge until a threshold concentration is reached that is sufficient to drive a protective response. This notion is consistent with the slow but progressive increase in Th2-associated responses observed during T. muris trickle (139). Further, damage-inducing microparticles have been previously shown to act as potent adjuvants capable of driving innate and antigen-specific Th2 immune responses in vivo comparable in efficacy to Alum (153,154), as does mechanical abrasion (155).…”
Section: Trickle Infectionsupporting
confidence: 81%
See 3 more Smart Citations
“…Therefore, during a trickle infection the concentration of these alarmins may increase with each subsequent challenge until a threshold concentration is reached that is sufficient to drive a protective response. This notion is consistent with the slow but progressive increase in Th2-associated responses observed during T. muris trickle (139). Further, damage-inducing microparticles have been previously shown to act as potent adjuvants capable of driving innate and antigen-specific Th2 immune responses in vivo comparable in efficacy to Alum (153,154), as does mechanical abrasion (155).…”
Section: Trickle Infectionsupporting
confidence: 81%
“…We have recently reported a detailed characterization of a long-term trickle infection with T. muris (139). By performing weekly infections of 20 embryonated T. muris eggs in C57BL/6 mice we observed infection kinetics that closely mimicked those seen in human T. trichiura infection.…”
Section: Trickle Infectionmentioning
confidence: 70%
See 2 more Smart Citations
“…During natural infection, T. muris is acquired by repeated low dose infections. Using a trickle infection approach in the laboratory, Glover et al (2019) showed that there was a steady build up in worm burden coincident with a dominant Th1 response until partial protective immunity was acquired due to the development of a stronger Th2 response. This suggests that adult parasites are present before effective IL-13-mediated immunity is acquired and thus copious p43 is secreted into the intestinal niche, which would bind IL-13 from the developing Th2 response, effectively delaying host protection.…”
Section: Excretory Secretory (Es) Proteins and Other Moleculesmentioning
confidence: 99%